Code-sharing policies are associated with increased reproducibility potential of ecological findings - Sánchez-Tójar, Alfredo; Bezine, Aya; Purgar, Marija; Culina, Antica (Peer Community Journal, 2025)

(untitled)
Software code (e.g., analytical code) is increasingly recognised as an important research output because it improves transparency, collaboration, and research credibility. Many scientific journals have introduced code-sharing policies; however, surveys have shown alarmingly low compliance with these policies. In this study, we expanded on a recent survey of ecological journals with code-sharing policies by investigating sharing practices in a comparable set of ecological journals without code-sharing policies. Our aims were to estimate code- and data-sharing rates, assess key reproducibility-boosting features, such as the reporting of software versioning, and compare reproducibility potential between journals with and without a code-sharing policy. We reviewed a random sample of 314 articles published between 2015 and 2019 in 12 ecological journals without a code-sharing policy. Only 15 articles (4.8%) provided analytical code, with the percentage nearly tripling over time (2015-2016:2.5%, 2018-2019:7.0%). Data-sharing was higher than code-sharing (2015-2016:31.0%, 2018-2019:43.3%), yet only eight articles (2.5%) shared both code and data. Compared to a comparative sample of 346 articles from 14 ecological journals with a code-sharing policy, journals without a code-sharing policy showed 5.6 times lower code-sharing, 2.1 times lower data-sharing, and 8.1 times lower reproducibility potential. Despite these differences, the key reproducibility-boosting features of the two journal types were similar. Approximately 90% of all articles reported the analytical software used; however, for journals with and without a code-sharing policy, the software version was often missing (49.8% and 36.1% of articles, respectively), and exclusively proprietary (i.e., non-free) software was used in 16.7% and 23.5% of articles, respectively. Our study suggests that journals with a code-sharing policy have greater reproducibility potential than those without. Code-sharing policies are likely to be a necessary but insufficient step towards increasing reproducibility. Journals should prioritize adopting explicit, easy-to-find, and strict code-sharing policies to facilitate researchers' compliance and should implement mechanisms such as checklists to ensure adherence.